Circulating catecholamines in acute asthma. Issue 6464 (26th January 1985) - Ind, P W; Causon, R C; Brown, M J; Barnes, P J
Abstract : Plasma catecholamine concentrations were measured in 15 patients (six male) aged 14-63 years attending the casualty department with acute severe asthma (peak expiratory flow 27% (SEM 3%) of predicted). Nine patients were admitted and six were not. The plasma noradrenaline concentration, reflecting sympathetic nervous discharge, was two to three times normal in all patients and was significantly higher in those who required admission compared with those discharged home (mean 7.7 (SEM 0.6) v 4.7 (0.5) nmol/l (1.3 (SEM 0.1) v 0.8 (0.08) ng/ml); p less than 0.001). Plasma adrenaline concentration, however, was not increased in any patient. This surprising failure of the plasma adrenaline concentration to increase during the stress of an acute attack of asthma was unexplained and contrasts with the pronounced rise in plasma adrenaline and noradrenaline concentrations in acute myocardial infarction, heart failure, and septicaemia. The failure of plasma adrenaline concentration to increase in acute asthma is unlikely to be explained by adrenal exhaustion, but it may be another example of impaired adrenaline secretion in asthma.